2020
DOI: 10.1177/2325967120973645
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Anterolateral Ligament of the Knee: An Evaluation of PubMed Articles From 2010 to 2019

Abstract: Background: The anterolateral ligament (ALL) of the knee remains a topic of interest. All aspects of the ligament, including its anatomy, biomechanics, imaging, and clinical importance, are areas for research among knee surgeons. Purpose: To evaluate the trends in research on the ALL of the knee, as indicated by studies indexed in PubMed from 2010 to 2019. Study Design: Cross-sectional study. Methods: We searched PubMed for article titles from January 1, 2010, to December 31, 2019, that included the term “ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…Despite several publications on the subject in the past decade worldwide and several publications by Brazilian authors on the subject 19 in this series of cases, we found only one report (0.97%) containing information on ALL. Thus, we understand that it would be appropriate to increase the active search for ALL during the evaluation of images by radiologists in orthopedics, enabling other data for the surgeon to define if the associated reconstruction between the ACL and ALL in the acute phase will be made and facilitate the authorization of the procedures and materials necessary by healthcare insurers.…”
Section: Discussioncontrasting
confidence: 56%
“…Despite several publications on the subject in the past decade worldwide and several publications by Brazilian authors on the subject 19 in this series of cases, we found only one report (0.97%) containing information on ALL. Thus, we understand that it would be appropriate to increase the active search for ALL during the evaluation of images by radiologists in orthopedics, enabling other data for the surgeon to define if the associated reconstruction between the ACL and ALL in the acute phase will be made and facilitate the authorization of the procedures and materials necessary by healthcare insurers.…”
Section: Discussioncontrasting
confidence: 56%
“…The anterolateral ligament (ALL), an anterolateral capsular structure located deep in the iliotibial band, was recently found to contribute to the rotational stability of the knee joint [5, 20, 25, 28, 30]. Accordingly, interest in this structure has increased, and numerous investigations have been conducted [31]. Although still controversial, anterolateral augmentation procedures (ALL reconstruction or lateral extra‐articular tenodesis) in conjunction with anterior cruciate ligament (ACL) reconstruction have been reported to control rotational stability effectively and to reduce graft failure rates [1, 9, 11, 12, 19, 27, 37, 38].…”
Section: Introductionmentioning
confidence: 99%
“…Third, no investigations on the possible influence of geometric factors that may affect tunnel collisions were conducted. Given the increasing incidence of anterolateral augmentation procedures [24, 31, 40], a well‐designed study that overcomes the potential limitations of these previous studies is required.…”
Section: Introductionmentioning
confidence: 99%
“…The anterolateral complex (ALC) of the knee has recently regained interest mainly due to the high revision rates in ACLR surgery, despite the recent concepts of anatomical and individualized ACL reconstruction and the vast improvements of fixation methods. [1][2][3][4] New evidence shows that ACLR revision rates remain unacceptably high, up to 18%, especially in the younger population. 5 These failures have a variety of factors, but one of the most concerning is the persisting anterolateral rotatory instability, which may not be fully restored with the current ACLR procedures.…”
Section: Introductionmentioning
confidence: 99%